Quantum transport in low-dimensional quantum wires and dots - Shangguan, Wangzuo. (2008)
We have investigated in this thesis the current-voltage response of such nanostructures, particularly that of systems made up of quantum dots, the so called "artificial atoms" which are essentially semiconductor heterostructure islands connected to source and drain. To be specific, what this thesis studies is, given a nanoscale device connected to two leads with a dc or ac voltage applied, the current response flowing through the system or its conductance, while there might be a variety of interactions in the device region, such as electron-electron and electron-phonon interaction. In addition, a time-dependent voltage will further complicate the problem considerably.